Peran Regulasi Diri dalam Belajar terhadap Prokrastinasi Akademik pada Siswa Madrasah Tsanawiyah - Yoga Achmad Ramadhan; Rio Adi Nugroho; Siti Khumaidatul Umaroh; Silvia Eka Mariskha (Jurnal Psikologi Integratif, 2023)
Academic procrastination is a detrimental behavior, including in the context of students at Madrasah Tsanawiyah. This study aims to analyze the role of self-regulated learning towards academic procrastination in Madrasah Tsanawiyah students. The study population was students from class VII to class IX at Madrasah Tsanawiyah IB, totaling 215 students consisting of 111 male students and 104 female students. Determination of research samples using cluster random sampling technique and obtained a sample of 140 students. The research data was obtained using a self-regulation scale in learning with a reliability value of 0.899 and an academic procrastination scale with a reliability value of 0.903. Simple linear regression was chosen as the research data analysis. Based on the results of the analysis it is known that self-regulation in learning is negatively related to academic procrastination with a regression coefficient of -0.817 with a value of p = 0.000 (p <0.05). The role of self-regulation in learning towards academic procrastination is shown by the R-Square of 0.421, meaning that the variable of self-regulated learning plays a role of 42.1% on the variable of academic procrastination. Prokrastinasi akademik merupakan perilaku yang merugikan, tidak terkecuali dalam konteks siswa di Madrasah Tsanawiyah. Penelitian ini bertujuan untuk emnganalisis peran regulasi diri dalam belajar terhadap prokrastinasi akademik pada siswa Madrasah Tsanawiyah. Populasi penelitian adalah para siswa kelas VII sampai dengan kelas IX Madrasah Tsanawiyah, berjumlah 215 orang yang terdiri dari 111 orang siswa laki-laki dan 104 orang siswa perempuan. Penetapan sampel penelitian menggunakan teknik cluster random sampling dan didapatkan sampel sebanyak 140 siswa. Data penelitian diperoleh menggunakan skala regulasi diri dalam belajar dengan nilai reliabilitas sebesar 0,899 dan skala prokrastinasi akademik dengan nilai reliabilitas sebesar 0,903. Regresi linier sederhana dipilih sebagai analisis data penelitian. Berdasarkan hasil analisis diketahui bahwa regulasi diri dalam belajar berhubungan negative dengan prokrastinasi akademik dengan koefisien regresi sebesar -0,817 dengan nilai p = 0,000 (p < 0,05). Peran regulasi diri dalam belajar terhadap prokrastinasi akademik ditunjukkan R-Square sebesar 0,421, bermakna variabel regulasi diri dalam belajar berperan sebesar 42,1% terhadap variabel prokrastinasi akademik.